Análise genômica da proteína P1 de isolados brasileiros e cubano do Papaia ringspot virus (PRSV) e interação vírus-planta utilizando como modelo o Soybean yellow shoot virus (SoyYSV) - Resende, Franciely Maria Pereira de (2019)
Papaya ringspot virus (PRSV) is one of the main viruses affecting papaya crops in Brazil and in other countries where this plant is grown. There are two naturally occurring strains in the field: PRSV-P that infects papaya and cucurbits and PRSV-W that infects cucurbits only. Their control is hindered by the fact that viruses have no curative control, papaya is a semi-perennial plant and the virus is easily spread in the fields by the Myzus persicae vector. In Brazil the virus has been controlled by roguing, which does not always present the expected results. In other countries PRSV has been satisfactorily controlled through the use of transgenic plants transformed with viral CP. However, there is some evidence that some regional PRSV isolates are capable of breaking the resistance of the transgenic plant, indicating that these plants should be transformed with genes from the isolates to which it will be exposed. Therefore, the isolates must be sequenced and analyzed, to provide support to breeding programs aiming to obtain pathogen resistance plant. In this work the P1 protein genes from five isolates from Brazil and one from Cuba were sequenced and analyzed in order to know their genetic identity. The genes were amplified using specific primer pairs and sent for sequencing at GENEWIZ, and analyzed using the NCBI BLAST (National Center for Biotechnology Information - NCBI, 2015), CLUSTAL W2 program. Phylogenetic trees were constructed using the MEGA 7.0 (Molecular Evolutionary Genetics Analysis) program. The identity between the Brazilian isolates and between them and the Cuban isolate was 87% or greater, and when compared with GenBank isolates the highest identity was observed with protein P1 of strain PRSV-W. On the other hand, PRSV-P isolates available from GenBank had a higher identity with isolates of PRSV-P strain. This shows that the Brazilian isolates analyzed have a peculiar characteristic, which differentiates them from most isolates already described in other parts of the world. In a second experiment, proteins from a member of the Potyviridae family, Soybean yellow shoot virus (SOyYSV) which was recently sequenced in Brazil, was chosen as a model to study virus-plant interaction because it is the only virus in this family that causes local lesion in papaya. Four genes of this virus were amplified and cloned by the Gateway system to be expressed via Agrobacterium tumefaciens in papaya plants: CP, HcPro, P1 and VPg. Twenty days after agroinfiltration the leaves of the plants were analyzed by RT-PCR and by observation under Epifluorescence microscope. None of the proteins induced local lesion in the agroinfiltrated leaves and all of them translocated and were detected in the leaves that expanded after agroinfiltration. This indicates that either the plant's HR reaction is elicited by other viral proteins or they act in combination to be recognized by the host plant.